New directions of development of artificial intelligence and the importance of their legal regulation - Sаrdоr Yusupоv (Peerian Journals Publishing, 2022)
Transportation, logistics, and supply chain management can benefit from digital solutions and artificial intelligence applications. However, the subject of human worker capabilities, motivation, and acceptability is critical to the actual success of such projects in businesses as well as in complete transportation systems and networks. This section provides context for an investigation of the framework conditions, current advancements, and regulatory requirements in the field of automation and robotics
Keywords: Artificial intelligence; European Commission; the US Federal Trade Commission; legal regulation,